Price Strategies of Exporters in Conditions of Crisis Caused by Pandemia - M. V. Dolgova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Price is the most important tool of company behavior on market, whose changes are caught immediately by customers, competitors and state structures. Adequate pricing can bring profit to the company and raise its competitiveness and stability on market. Unfortunately, rather often price decisions of home exporters working on non-raw material markets are only a response to competitors’ steps and they aim at reaching tactical, momentary but not strategic goals. Companies usually try to use the same price strategies on foreign markets as they use on national market. In conditions of the global crisis, uneven introduction of isolation regime and border closing by countries, breaking supply chains, bankruptcy or closure of national companies Russian exporters face the loss of distribution channels developed earlier. On the other hand, in these conditions they get an opportunity not only to settle on developed markets nut to penetrate new overseas markets in such segments, where the work of local companies was cut or shut down. In any case home exporters should think over their price strategy on foreign market and research changes in customer preferences, in their perception of company product value. The author gives recommendations aimed at improving exporters’ pricing in conditions of 2020 crisis on the basis of analyzing customers in view of their contribution to the company profit.